CO2 and Water Vapor Exchange across Leaf Cuticle (Epidermis) at Various Water Potentials. - Boyer, J. S. (1997)
Cuticular properties affect the gas exchange of leaves, but little is known about how much CO2 and water vapor cross the cuticular barrier or whether low water potentials affect the process. Therefore, we measured the cuticular conductances for CO2 and water vapor in grape (Vitis vinifera L.) leaves having various water potentials. The lower leaf surface was sealed to force all gas exchange through the upper surface, which was stoma-free. In this condition both gases passed through the cuticle, and the CO2 conductance could be directly determined from the internal mole fraction of CO2 near the compensation point, the external mole fraction of CO2, and the CO2 flux. The cuticle allowed small amounts of CO2 and water vapor to pass through, indicating that gas exchange occurs in grape leaves no matter how tightly the stomata are closed. However, the CO2 conductance was only 5.7% of that for water vapor. This discrimination against CO2 markedly affected calculations of the mole fraction of CO2 in leaves as stomatal apertures decreased. When the leaf dehydrated, the cuticular conductance to water vapor decreased, and transpiration and assimilation diminished. This dehydration effect was largest when turgor decreased, which suggests that cuticular gas exchange may have been influenced by epidermal stretching.